Biofilm Formation by Environmental and Clinical Isolates of Pseudomonas aeruginosain vitro - Ghada Mohammed Saleh; Abass Mohammed (World Journal of Experimental Biosciences, 2020)
Biofilm builds when bacteria adhere to surfaces in aqueous environments and begin to excrete a slimy, glue-like substance that can anchor them to all kinds of material – such as metals, plastics, soil particles, medical implant materials, and most significantly, human or animal tissue. Most bacteria have a good ability to form biofilm. The studies that cover the compression of biofilm formation by environmental and clinical isolates of Pseudomonas aeruginosa are very scanty. The present study aimed to measure the biofilm formation by clinical and environmental isolates of P. aeruginosa to form biofilm onto polystyrene microtiter plates. Two clinical isolates of P. aeruginosa (CPa3 and CPa4) that were isolated from patients suffering from respiratory tract infection and two environmental isolates of P. aeruginosa (EPa1 and EP2) that were isolated from soil contaminated with oil wastes were included in the current study. The micro-dilution and spectrophotometric method was used to measure the biofilm formation of P. aeruginosa isolates to polystyrene microtiter plates. The optical density of the released crystal violates stain in the case of clinical isolates of P. aeruginosa was 0.28 ± 0.11, while this value was 0.13 ± 0.01 in the case of environmental isolates of P. aeruginosa. The present study provided the ability of clinical isolates to form biofilm higher than the ability of environmental isolates to form biofilm.
Keywords: Biofilm, Clinical isolates, Environmental isolates, Pseudomonas aeruginosa